Food safety and young consumers: Testing a serious game as a risk communication tool. (April 2016) - Crovato, S.; Pinto, A.; Giardullo, P.; Mascarello, G.; Neresini, F.; Ravarotto, L.
Abstract: Raising consumers' awareness about food safety issues is one of the primary objectives of Italian public health organizations. New dynamic and interactive tools, based on web applications, are already playing a leading role in health promotion campaigns targeted at adolescents. Among the web-based tools specifically designed for young people, educational videogames have proved especially effective in furthering learning and disseminating information, as they arouse adolescents' interest and curiosity. When a number of cases of Haemolytic-uraemic syndrome (HUS) were reported in 2010, particularly among children, the Italian Ministry of Health stressed the need to implement communication initiatives aimed at raising consumers' awareness of the potential risks associated with raw milk consumption at home. The pilot study described in the article is a relevant example of educational projects implemented in Italy, oriented to transmit knowledge about food risks to young consumers (aged 16–18). To provide correct information on safe milk handling practices and to reduce health issues, including serious ones, the videogame "A mysterious poisoning" was developed. This tool was administered online to 359 upper secondary school students from four different provinces in Italy. The videogame covered all stages of the milk supply chain, from stable to table, and enabled players to identify the crucial moments when milk can be contaminated and to discover safe milk handling practices. By completing a series of tasks, students helped a detective discover the cause of a food poisoning outbreak. This videogame provided an opportunity for students to test their knowledge of the product and to receive more detailed and accurate information. Data collected through two structured questionnaires that were administered before and after the controlled use of the videogame showed that this serious game was capable of changing players' perception of risk exposure and their cognitive associations, particularly increasing their levels of knowledge about the risks associated with raw milk consumption. Highlights: Students indicated videogame as the most suitable tool for communicating food risk. The game "A mysterious poisoning" was built through the students' indications. The serious game modified players' perception of food risk exposure. Cognitive associations with food risk changed after players' performance. Players' knowledge about milk and raw milk increased after the exposure to the tool.